Empsychoi logoi--religious innovations in antiquity : studies in honour of Pieter Willem van der Horst - Horst, Pieter Willem van der.; Houtman, Alberdina.; Jong, Albert de, 1966-; Weg, Magdalena Wilhelmina Misset-van de, 1943- (Ancient Judaism and Early Christianity, 2008)
The fact that religions show internal variation and develop over time is not only a problem for believers, but has also long engaged scholars. This is especially true for the religions of the ancient world, where the mere idea of innovation in religious matters evoked notions of revolution and destruction. With the emergence of new religious identities from the first century onwards, we begin to find traces of an entirely new vision of religion. The question was not whether a particular belief was new, but whether it was true and the two were no longer felt to be mutually exclusive. The present volume brings together articles that study this transformation, ranging from broad overviews to detailed case-studies.